Peace without women does not go! Womens struggle for inclusion in Colombias peace process with the FARC - Lina M. Céspedes-Báez; Felipe Jaramillo Ruiz (Universidad de Los Andes, 2018)
In this study, we analyze the tactics deployed by Colombian womens rights NGOs, movements, and advocacy groups to challenge masculinism in the peace negotiations between the Colombian government and the former Colombian guerrilla Revolutionary Armed Forces (FARC) held in Havana.1 By drawing on the literature on womens participation in peace and transitional justice processes, the research assesses the presence of women in Colombias peace talks, the way womens movements articulated their demands, the role of the sub-commission on gender, and the manner in which gender was introduced in the drafts of the peace agreement and in the document the parties to the negotiation signed in Cartagena in September 2016.